Preparation of electrospun nanofibrous polycaprolactone scaffolds using nontoxic ethylene carbonate and glacial acetic acid solvent system. Issue 8 (10th August 2019) - Zhang, Yu; Ullah, Ismat; Zhang, Wancheng; Ou, Hao; Domingos, Marco; Gloria, Antonio; Zhou, Jinge; Li, Wenchao; Zhang, Xianglin
ABSTRACT: In recent years, solution electrospinning has attracted the interest of researchers due to the possibility to design nanofibrous scaffolds with large surface area to volume ratios. Polycaprolactone (PCL), because of its biocompatibility and easy processability, has been widely used to develop electrospun structures for tissue engineering. However, the use of organic solvents and the poor PCL solution stability still hinder the development of the solution electrospinning process. The relatively benign glacial acetic acid (GAC) as a solvent of PCL was used to fabricate microfibrous fibers or beaded fibers. Thus, ethylene carbonate (EC) as a nontoxic assistant solvent was added to the PCL/GAC solution to successfully fabricate electrospun nanofibrous PCL scaffolds. The stability of the PCL/GAC/EC solution system was demonstrated as the viscosity, which showed no significant change during 48 h. The ultrafine PCL fiber diameter decreased as EC concentration was increased from 0 to 9 vol% and started to slightly increase when EC concentration increased beyond 9 vol%. MTT assay evidenced that MC3T3‐E1 cells on the nanofibrous PCL scaffolds exhibited a better enhancement on cell proliferation. In summary, EC was added in PCL/GAC to establish a stable and low toxic solution electrospinning system, which provides promising strategy in tissue engineering field. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48387. Abstract : Polycaprolactone (PCL), because of its biocompatibility and easy processability, has been widely used to develop electrospun structures for tissue engineering. However, the use of organic solvents and the poor PCL solution stability still hinder the development of the solution electrospinning process. The relatively benign glacial acetic acid (GAC) as a solvent of PCL was used to fabricate microfibrous fibers or beaded fibers. Thus, ethylene carbonate (EC) as a nontoxic assistant solvent was added to the PCL/GAC solution to successfully fabricate electrospun nanofibrous PCL scaffolds.